Jupiter Elevation Angle Determination at Baghdad Location - M. Abood, Kamal; J. Kahdom, Mourtada; F. Kahdome, Zeina (Iraqi Journal of Science, 2023)
In this paper the elevation angle of Jupiter at Baghdad location according to its coordinate for the period (2005-2020) has been studied. The Radio Jove pro. Edition program is used to achieve the Jupiter elevation angle at this time period. In 2007, 2008 the path of Jupiter is appeared near the horizon when the monitor trying to observe it. While in 2013, 2014 it's reached its maximum value then its return to reached its minimum value at 2019, 2020 according to the position of Jupiter in Baghdad for this period.